Distance learning technologies at the postgraduate stage of professional development of pharmacists - M. O. Avramenko; N. O. Tkachenko; Yu. Yu. Riabokon; O. A. Bigdan (Zaporozhye State Medical University, 2021)
Today, pharmaceutical education has to respond flexibly, dynamically and adequately to social transformations by developing new educational services, teaching technologies and organizing the training process. In response to the demand of the time, postgraduate professional education strives to meet the current needs; a new concept of increasing the effectiveness of education and the professional level of specialists has been formed: lifelong learning is impossible without the use of information and communication technologies. The aim of the work is to identify the features of the organization of the training process of pharmaceutical professionals at the postgraduate stage at Zaporizhzhia State Medical University (ZSMU) and to outline its problematic issues with further identification of possible ways of improvement in the context of continuing professional development (CPD). Materials and methods. The study was grounded on the experience of organizing the training of pharmaceutical interns, students of advanced training cycles at the Faculty of Postgraduate Education of ZSMU for the last 10 years, reporting and other accounting documents, regulations on higher pharmaceutical education at various levels. The methods of analysis and synthesis, grouping, deduction, logic and generalization are used in the work. Results. The postgraduate phase of СPD of pharmaceutical specialists is aimed at improving professional competencies and allows the specialist to maintain or improve the standards of professional activity in accordance with the needs of health care. Training of pharmaceutical specialists at the Faculty of Postgraduate Education is practiced both face-to-face and distantly, using distance learning technologies in a specialized web environment, grounding on modern psychological, pedagogical and information and communication technologies (basic is Microsoft Office 365 and others). This format of education stimulates students to unleash their potential, increase the level of self-organization and self-management, deepens professional competencies by improving the communication component. The management of ZSMU, driven by social responsibility, constantly works on improving the quality of educational services, including those of the postgraduate stage. Conclusions. According to the results of critical analysis of the experience of training pharmaceutical interns and students of advanced training cycles at FPE of ZSMU for the last 10 years, reporting and regulatory documentation, features of the educational process of pharmaceutical specialists at the postgraduate stage are identified, its problematic issues are outlined and ways to solve them in the context of СPD are deteermined.